Iconic Gestures Facilitate Discourse Comprehension in Individuals With Superior Immediate Memory for Body Configurations - Wu, Ying Choon; Coulson, Seana (Psychological Science, 2015)
To understand a speaker’s gestures, people may draw on kinesthetic working memory (KWM)—a system for temporarily remembering body movements. The present study explored whether sensitivity to gesture meaning was related to differences in KWM capacity. KWM was evaluated through sequences of novel movements that participants viewed and reproduced with their own bodies. Gesture sensitivity was assessed through a priming paradigm. Participants judged whether multimodal utterances containing congruent, incongruent, or no gestures were related to subsequent picture probes depicting the referents of those utterances. Individuals with low KWM were primarily inhibited by incongruent speech-gesture primes, whereas those with high KWM showed facilitation—that is, they were able to identify picture probes more quickly when preceded by congruent speech and gestures than by speech alone. Group differences were most apparent for discourse with weakly congruent speech and gestures. Overall, speech-gesture congruency effects were positively correlated with KWM abilities, which may help listeners match spatial properties of gestures to concepts evoked by speech.